(untitled) (BIBECHANA, 2022)
Using the density functional theory formalism, electronic and magnetic properties of double perovskites Ca2MnIrO6 are investigated. We found ferrimagnetic ground state with half-metallic nature in Ca2MnIrO6. The electron-correlation, crystal distortion, and spin-orbit coupling (SOC) plays significant role in dictating the electronic properties in this system. From the density of states calculations, a strong hybridization were noted between O-2p, Ir-5d and Mn-3d states resulting Ca2MnIrO6 to half-metal (HM) with metallic state in spin up channel and insulating state in spin-down channel. The HM state persists even when SOC is taken into account, though the spin-polarization reduces slightly. We thus predict Ca2MnIrO6 as a new HM ferrimagnet which can be useful for modern technological applications. We further investigated the Curie temperature of Ca2MnIrO6 by calculating the spin-exchange coupling parameters. Our results are found to be comparable with other perovskites. BIBECHANA 19 (2022) 127-132